Sphingolipids contribute to acetic acid resistance in Zygosaccharomyces bailii. Issue 4 (10th December 2015) - Lindahl, Lina; Genheden, Samuel; Eriksson, Leif A.; Olsson, Lisbeth; Bettiga, Maurizio
ABSTRACT: Lignocellulosic raw material plays a crucial role in the development of sustainable processes for the production of fuels and chemicals. Weak acids such as acetic acid and formic acid are troublesome inhibitors restricting efficient microbial conversion of the biomass to desired products. To improve our understanding of weak acid inhibition and to identify engineering strategies to reduce acetic acid toxicity, the highly acetic‐acid‐tolerant yeast Zygosaccharomyces bailii was studied. The impact of acetic acid membrane permeability on acetic acid tolerance in Z. bailii was investigated with particular focus on how the previously demonstrated high sphingolipid content in the plasma membrane influences acetic acid tolerance and membrane permeability. Through molecular dynamics simulations, we concluded that membranes with a high content of sphingolipids are thicker and more dense, increasing the free energy barrier for the permeation of acetic acid through the membrane. Z. bailii cultured with the drug myriocin, known to decrease cellular sphingolipid levels, exhibited significant growth inhibition in the presence of acetic acid, while growth in medium without acetic acid was unaffected by the myriocin addition. Furthermore, following an acetic acid pulse, the intracellular pH decreased more in myriocin‐treated cells than in control cells. This indicates a higher inflow rate of acetic acid and confirms that the reduction in growth of cells cultured with myriocin in the medium with acetic acid was due to an increase in membrane permeability, thereby demonstrating the importance of a high fraction of sphingolipids in the membrane of Z. bailii to facilitate acetic acid resistance; a property potentially transferable to desired production organisms suffering from weak acid stress. Biotechnol. Bioeng. 2016;113: 744–753. © 2015 Wiley Periodicals, Inc. Abstract : Weak acids are troublesome inhibitors restricting efficient microbial conversion of lignocellulosic biomass to desired products. In silico molecular dynamic simulations in combination with in vivo techniques were used to demonstrate that the high sphingolipid content in the plasma membrane of Z. bailii reduces the acetic acid diffusion rate, thereby contributing to its high acetic acid tolerance. In addition, the effect of changes in acetic acid diffusion rate was considered in relation to other parameters influencing acetic acid tolerance.